Perancangan Aplikasi Presensi Mahasiswa Teknik Indutrsi UNSIKA Menggunakan QR-Code dan Geotagging Berbasis Android - Siti Nadia Mahmuda; Ade Momon S (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
Currently, the development of technology is very rapid and has a positive impact on institutions or individuals who use it. In the world of education, many Indonesian educational institutions have used information technology to assist the teaching and learning process or the administrative processes contained in these institutions. One of the technologies applied is Android-based attendance. In academic activities in lectures, student attendance is carried out so that lecturers can know the presence of their students in academic activities carried out on campus. Based on the research that has been done by the author, the results of an android-based of presences application design for the Industrial Engineering Study Program of the Singaperbangsa Karawang University can be used by students to make attendance in each course and apply for student permits. This android-based student attendance application design can reduce the inaccuracy and cheating of student attendance data.